Anatomical Feasibility Study on Novel Ascending Aortic Endograft With More Proximal Landing Zone for Treatment of Type A Aortic Dissection - Li, Xiaoye; Zhu, Longtu; Zhang, Lei; Song, Chao; Zhang, Hao; Xia, Shibo; Guo, Wenying; Jing, Zaiping; Lu, Qingsheng (Frontiers in Cardiovascular Medicine, 2022)
Abstract Objective: Type A aortic dissection (TAAD) is associated with high morbidity and mortality with open surgery as the best treatment option. Development of endovascular repair devices for TAAD will benefit those patients deemed unfit for open surgery. In this study, we performed thorough investigation of anatomical features in Asian TAAD patients to learn about patient eligibility of a novel ascending aortic endograft. Methods: Computed tomography angiography (CTA) images of TAAD cases at our institution from January 2015 to November 2021 were reviewed and three-dimensional reconstructions were performed with Endosize software (Therenva, Rennes, France). Anatomic structures including length measured along centerline and greater/lesser curvature, ascending aorta/aortic root dimensions, as well as location of entry tear and extent of dissection were analyzed. Results: A total of 158 patients were included (median age 58 years, interquartile range [IQR], 30-76 years; 115 males, 72.8%). In 99 cases (62.7%), the entry tear was distal to the sinotubular junction (STJ). In 106 cases (67.1%), the pathology proximally extended into the aortic root, which was intramural hematoma in 37 cases (23.4%), and the aortic root was free from the pathology in 52 cases (32.9%). The median distance from the STJ to the proximal edge of ostium of IA measured along the centerline was 65mm (IQR, 58-74mm). The median distance from the distal edge of higher coronary ostium to the STJ was 7.95mm (IQR, 5.625-10.9mm). The bare metal stent part was set between the edge of the higher coronary ostium and STJ. In our series, 63 cases (39.9%) had this distance >10mm. The relative difference was less than 20% between STJ and proximal edge of ostium of IA in 92 cases (58.2%), respectively. Ascending aorta radius of curvature was 52.2mm (IQR, 43.7-63.7mm). Conclusions: Our study demonstrates that 56.3% of TAAD cases would be amenable to endovascular repair with the novel ascending aortic endograft with sufficient landing zone free of dissected aorta.